Biomimetic apatite formation on different polymeric microspheres modified with calcium silicate solutions - Leonor, I. B. (2006)
Proceedings of the 18th International Symposium on Ceramics in Medicine, The Annual Meeting of the International Society for Ceramics in Medicine (ISCM), Kyoto, Japan, 5-8 December 2005. Published in : Key Enggineering Materials, vol. 309 - 311